2007
DOI: 10.1080/02652030701305454
|View full text |Cite
|
Sign up to set email alerts
|

Allergenicity and allergens of amphipods found in nori (dried laver)

Abstract: Gammaridean and caprellid amphipods, crustaceans of the order Amphipoda, inhabit laver culture platforms and, hence, are occasionally found in nori (dried laver) sheets. Amphipods mixed in nori may cause allergic reactions in sensitized patients, as is the case with other crustaceans, such as shrimp and crab, members of the order Decapoda. In this study, dried samples of amphipods (unidentified) found in nori and fresh samples of gammaridean amphipod (Gammarus sp., not accurately identified) and caprellid amph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…For example, contaminants such as the parasite Anisakis, if present, can cause severe allergic reactions [54]. The eight allergens from this parasite currently characterized include tropomyosin, which cross-reacts with shellfish allergens, as well as 272 Food allergy Tropomyosin [27] paramyosin and different protease inhibitors [54][55][56][57][58] ( Table 4). A recent study demonstrated that these parasites could also cause allergic sensitization among fish-processing workers [59].…”
Section: Allergens In the Different Seafood Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, contaminants such as the parasite Anisakis, if present, can cause severe allergic reactions [54]. The eight allergens from this parasite currently characterized include tropomyosin, which cross-reacts with shellfish allergens, as well as 272 Food allergy Tropomyosin [27] paramyosin and different protease inhibitors [54][55][56][57][58] ( Table 4). A recent study demonstrated that these parasites could also cause allergic sensitization among fish-processing workers [59].…”
Section: Allergens In the Different Seafood Groupsmentioning
confidence: 99%
“…The recombinant protein was subsequently produced and identified as a myosin light chain with high amino acid similarity to Bla g 8 from cockroaches. In addition, a sarcoplasmatic calcium-binding protein was identified as allergen in black tiger shrimp [25] and tropomyosin in two krill species [26] and an amphipod [27].…”
Section: Allergens In the Different Seafood Groupsmentioning
confidence: 99%
“…The red algae genus, Porphyra yezoensis (i.e., nori), is one of the most commonly consumed seaweeds in East and Southeast Asia, and its consumption is rapidly spreading throughout the world. In Japan, approximately nine billion nori sheets are produced per year and utilized for various culinary purposes (e.g., sushi, soups, and salads) ( 7 ). Nori has been gaining a great deal of attention due to its various biological activities (e.g., anti-allergic activity, chemoprotective activity, anti-inflammatory activity, and detoxification activity) ( 8 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tabel 6 menunjukkan nilai kuat tarik berkisar antara 2-12,1 N. Semakin kecil ukuran mesh akan meloloskan lebih banyak.Terjadinya kekuatan tarik dikarenakan adanya saling interaksi antara ikatan hidrogen antar molekul CH 2 OH pada struktur agar dan OH. Kuat tarik menunjukkan ketahanan nori (Motoyama et al, 2007).…”
Section: Kekuatan Tarikunclassified